A new biocompatible delivery scaffold containing heparin and bone morphogenetic protein 2 - Thanyaphoo Suphannee; Kaewsrichan Jasadee (Acta Pharmaceutica)
Silicon-substituted calcium phosphate (Si-CaP) was developed in our laboratory as a biomaterial for delivery in bone tissue engineering. It was fabricated as a 3D-construct of scaffolds using chitosan-trisodium polyphosphate (TPP) cross-linked networks. In this study, heparin was covalently bonded to the residual -NH2 groups of chitosan on the scaffold applying carbodiimide chemistry. Bonded heparin was not leached away from scaffold surfaces upon vigorous washing or extended storage. Recombinant human bone morphogenetic protein 2 (rhBMP-2) was bound to conjugated scaffolds by ionic interactions between the negatively charged SO42- clusters of heparin and positively charged amino acids of rhBMP-2. The resulting scaffolds were inspected for bone regenerative capacity by subcutaneous implanting in rats. Histological observation and mineralization assay were performed after 4 weeks of implantation. Results from both in vitro and in vivo experiments suggest the potential of the developed scaffolds for bone tissue engineering applications in the future.